Microstructural Characteristics of Eri Silk Fibre in Different Layers of Cocoon - Debasis Chattopadhyay; Arijit Chakraborty; S. M. Chatterjee (Journal of Natural Fibers, 2023)
Five layers, i.e. floss, upper, middle, lower and pelade, exist in cocoon shell from outer to inner portion. An attempt has been made for assessment of microstructural characteristics of eri silk fiber in different layers of cocoons. Wide angle x- ray diffraction assessment revealed increase of crystallinity as well as degree of orientation and decrease in crystal size besides lattice spacing remains at par from floss to pelade layers. So, there is an improvement of single fibre tenacity and initial modulus from outer to inner position of cocoon’s shell. AFM assessment depicts increase in surface roughness of silk fibre from floss to pelade portion as observed from surface topography and root mean square average (Rq) of height deviation values. Descending trend of single fibre length and diameter were observed from floss to pelade layers along with significant reduction in lower and pelade layers vis-à-vis floss, upper and middle layers. Fibre quality index (FQI) can be measured from average single fibre length, fibre fineness and tenacity in five different layers. Expression has been derived for prediction of yarn tenacity from FQI and yarn count and good correlation exists between predicted and actual values.